2008
DOI: 10.1002/bdrb.20143
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile toxicity assessment of d,l‐methylphenidate in rats

Abstract: BACKGROUND:The oral administration of d,l-methylphenidate (MPH) was designed to encompass the major part of postnatal development in the rat and to evaluate potential chronic effects. METHODS: Wistar Hannover rats were crossfostered on postpartum day 0 (day of birth) and were administered MPH at doses of 5, 50, and 100 mg/kg/day (mpkd) on postpartum days 7 to 70. Clinical signs, body weight, food consumption, developmental, behavioral, clinical/ anatomic pathology, toxicokinetic, and fertility evaluations were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…MPD bind to dopamine (DA) transporter (DAT) that results in an increase DA concentration in the synaptic cleft (Volkow et al, 2005) therefore MPD is consider as an indirect dopamine (DA) agonist (Challman and Lipsky, 2000; Gatley et al, 1999; Solanto, 1998), DA functioning varies by sex and age which may result in the effect of MPD being different in male and female of different ages (Cornforth et al, 2010). Prenatal cocaine dampened behavioral responses to MPD in male and female adolescent rats exhibits sex differences in their response to the drug (Torres-Reveron and Dow-Edwards, 2006), as well as using incentive processing (Brenhouse et al, 2009), anxiety-related behavior (Vendruscolo et al, 2008), juvenile toxicity assessment (Beckman et al, 2008; Teo et al, 2002), impairment of attention (Rezvani et al, 2009), behavioral performance (Wagner et al, 2007), and circadian activity pattern (Algahim et al, 2009; Lee et al, 2009) procedures. However, controversial observations following MPD administration among the sexes were reported (Cornforth et al, 2010; Dafny and Yang, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…MPD bind to dopamine (DA) transporter (DAT) that results in an increase DA concentration in the synaptic cleft (Volkow et al, 2005) therefore MPD is consider as an indirect dopamine (DA) agonist (Challman and Lipsky, 2000; Gatley et al, 1999; Solanto, 1998), DA functioning varies by sex and age which may result in the effect of MPD being different in male and female of different ages (Cornforth et al, 2010). Prenatal cocaine dampened behavioral responses to MPD in male and female adolescent rats exhibits sex differences in their response to the drug (Torres-Reveron and Dow-Edwards, 2006), as well as using incentive processing (Brenhouse et al, 2009), anxiety-related behavior (Vendruscolo et al, 2008), juvenile toxicity assessment (Beckman et al, 2008; Teo et al, 2002), impairment of attention (Rezvani et al, 2009), behavioral performance (Wagner et al, 2007), and circadian activity pattern (Algahim et al, 2009; Lee et al, 2009) procedures. However, controversial observations following MPD administration among the sexes were reported (Cornforth et al, 2010; Dafny and Yang, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of a case-by-case approach to study design is emphasized in both EMA and FDA regulatory guidance and also recommended by a broad group of scientists with a common interest in juvenile animal studies (EMA, 2008;FDA, 2006;Hurtt et al, 2004). Several examples of juvenile animal study designs are available in the public literature (Rigdon et al, 1989;Hurtt et al, 2004;Beckman et al, 2008;Cappon et al, 2009;Anderson et al, 2009) and some examples are presented below. The examples summarize experience in dealing with safety assessment of new therapeutic candidates or modalities (e.g., inhaled products) for the juvenile patient population.…”
Section: Case Studies: Application Of Data Review and Decision Makingmentioning
confidence: 99%
“…The value of performing a targeted study is the detailed evaluation that is possible when focusing on specific organs of concern. Several examples of targeted study designs are available in the public literature (Beckman et al, 2008;Rigdon et al, 1989), and hypothetical case studies also have been used to illustrate this concept (Anderson et al, 2009;Hurtt et al, 2004). The primary factors to consider when designing a targeted juvenile animal study are: (1) ensure that the organ system of concern is undergoing similar developmental processes during the postnatal period as in the intended pediatric population; (2) define the age of exposure in the experimental species to ensure that the organ systems of concern are at the same stage of development in the animal species as in the intended human pediatric population; and (3) ensure that the appropriate endpoints are included to enable an in-depth investigation of the organ system of concern.…”
Section: Targeted Study Designsmentioning
confidence: 99%
“…The design of nonclinical studies in juvenile animals will vary depending on the therapeutic target, findings observed in adult human studies, and previous animal studies as well as on the age range of the prospective patient population. This type of science-driven study design approach has been successfully used to identify age-related differences in toxicity based on the developmental process occurring during postnatal development (Atchison et al, 1982;Beckman et al, 2008;Friedmann, 2002;Gabel et al, 1985;Karanth and Pope, 2003;Rice, 1988;Rigdon et al, 1989;Vorhees et al, 2000), and some of these examples were used as justification for the case-by-case approach described in the FDA guidance (FDA, 2006).…”
Section: Introductionmentioning
confidence: 99%